Adaptasi dan komunikasi mahasiswa asal papua dalam interaksi sosial di kota malang - Hakim, Abdul (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
When people from different cultural backgrounds talk to each other, this is known as intercultural communication. These differences can cause problems such as culture shock. The use of communication patterns in the context of cultural diversity among ethnic Papuan students at Kanjuruhan University Malang is quite diverse, including multidirectional communication patterns. The purpose of this study is to find out how ethnic Papuan students who experience culture shock communicate in social situations. The objects used in this study are ethnic Papuan students in semester 2, 4, 6 and 8 at Kanjuruhan University Malang, with each taking two students in each semester. Interviews, observations, literature studies, and documentation were used as data collection techniques. From the results of the study, it can be concluded that the culture shock of Papuan students affects how communication patterns are used. One-way communication patterns are applied by 2nd semester students with culture shock experienced such as language barriers or accents as well as self-conditions that include feelings of fear, inferiority or lack of confidence. Furthermore, two-way communication patterns are applied by 4th semester students and 6th semester students, students who use this communication pattern have begun to be able to overcome the culture shock they experienced. And finally, the multidirectional communication pattern was applied by 8th semester and 6th semester students, students who applied this pattern were able to overcome the culture shock they had previously experienced.